Spektralno selektivne površine za sončne zbiralnike in sončne fasade zgradb - Surca, Angelja Kjara (Vakuumist, 2001)
Herein we report the prepaation of spectrally selective Ti;CuCoMnO sup x-I (synthesis I) in CuCoMnO sup x-II (synthesis II) coatingsfor solar collectors and solar building façades. All coatings were made using sol-gel synthesis routes and dip-coating technique. Solar absorptances were in the range of 0.71 < alpha sup s < 0.95 for both kinds of coatings, while thermal emittances were between 0.01 < epsilon sup T < 0.11. the best properties were found for CuCoMnO sup x-II coatings prepared by the second snthesis route, i.e. solar absorptance alpha sup s=0.95 and thermal emittance epsilon sup T=0.04. The stability of coatings was considerably improved by the deposition of protective silica over-coatings, which only slightly influenced the spectrally selective properties of CuCoMnO sp x-II (alpha sup s=0.92, epsilon sup T=0.045).
Keywords: sončne celice; tanke plasti; spektralna selektivnost; kovinski oksidi; elektrokromizem; premazi; oksidni filmi